The effect of extended continuous nursing strategy applied to patients with mild brain injury on their quality of life and self-efficacy - Zhang, Li; Ma, Yanmei; Liu, Jia; Cai, Miao; Zheng, Wenqiu (Frontiers in Surgery, 2022)
Postoperative rehabilitation of craniocerebral injury requires a long process and has many complications. In addition, patients with severe craniocerebral injury are usually accompanied by impaired nervous system function, which will affect the patients’ normal life and work in a period of time after surgery. Reasonable rehabilitation nursing plays an active role in restructuring central nervous system function and coordinating muscle and joint activities. Since the rehabilitation of cerebral trauma is a long process, how to ensure the patients to carry out limb and brain function as well as self-care ability and self-care skills according to the rehabilitation exercise plan and intervention measures formulated before discharge has aroused hot debate. This study analyzed the impact of out-of-hospital continuous nursing strategy applied to patients with mild cerebral trauma on their quality of life and self-efficacy level.